Malaysia Economic Monitor, December 2017 : Turmoil to Transformation, 20 Years after the Asian Financial Crisis - World Bank Group (World Bank, Washington, DC, 2017)
The aim of the Malaysia Economic Monitor (MEM) is to foster better-informed policy analysis and debate regarding the key challenges that Malaysia faces in its endeavor to achieve rapid, inclusive and sustainable economic growth. The MEM consists of two parts: Part 1 presents a review of recent economic developments and a macroeconomic outlook. Part 2 focuses on a selected special topic that is key to Malaysia’s development prospects, particularly as the country moves towards becoming a high-income economy.